Gender, welfare state, and the market : towards a new division of labour - Boje, Thomas P., 1944-; Leira, Arnlaug (Routledge research in gender and society, 2005)
This volume represents the present state of the art in theoretical debate in welfare state scholarship, drawing on research from western Europe, North America and Japan.